Scaling carbon fluxes from eddy covariance sites to globe: Synthesis and evaluation of the FLUXCOM approach - Jung, Martin (2021)
This research has been supported by the European Space Agency (grant no. ESRIN/4000123002/18/I-NB), the National Science Foundation under cooperative agreement no. 1852977 and the U.S. Department of Energy (no. DE-SC0016323)